The system of administrative courts in Indonesia / Normawati Hashim - Normawati , Hashim (1998)
With the proliferation and explosion of administrative apparatus, the growth and expansion of the powers and functions of the administration in Indonesia, individuals' rights are increasingly being encroached upon by administrative actions or decisions. The rel!Jctance of the Indonesian courts1 to award damages to the citizens for unlawful acts of the administrators prior to 1991 has led to an urgent need to establish administrative courts which are independent of the government or executive.